Slope morphologies offshore Dakhla (SW Moroccan margin) - Benabdellouahed Massinissa; Baltzer Agnes; Rabineau Marina; Aslanian Daniel; Sahabi Mohamed; Germond Fabien; Loubrieu Benoit; Biari Youssef (BSGF - Earth Sciences Bulletin, 2016)
This study explores a portion of the West African margin at the junction between two well-known segments offshore Dakhla and offshore Mauritania with destructional architecture characterized by giant slides. In between these two segments, the Dakhla segment has historically been described as a constructional section. During an oceanographic Dakhla cruise (2002), high resolution seismic data, swath bathymetry and imagery were acquired around latitude 23°N, offshore Dakhla. This new data set reveals the existence of varied and complex morphologies on the continental slope, interpreted as a “shallot-shaped” canyon, seafloor depressions or pockmarks, ridges and scarps. These morphologies are interpreted as clues of sedimentary transfers and rupture processes. A scenario is proposed for the development of these different sedimentary morphologies.